2001
DOI: 10.1097/00002480-200107000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Recirculation in Double Lumen Catheter Veno-Venous Extracorporeal Membrane Oxygenation Measured by an Ultrasound Dilution Technique

Abstract: Recirculation is a limiting factor for oxygen delivery in double lumen catheter veno-venous extracorporeal membrane oxygenation (DLVV-ECMO). This study compares three different methods for the determination of the recirculation fraction during double lumen catheter veno-venous ECMO at ECMO flow rates of 150, 125, 100, 75, and 50 ml/kg.min in nine lambs: (1) an ultrasound dilution method, in which the change in ultrasound velocity in blood after injection of a saline bolus as a marker is used for determination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 13 publications
1
47
0
Order By: Relevance
“…This is a factor that limits oxygen delivery to the patient and does not contribute to the oxygenation of the patient. 7 Recirculation has been found to be 53% at a bypass flow of 400 ml/min. Generally, as recirculation increases, the efficacy to the systemic circulation decreases in terms of oxygen delivery.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is a factor that limits oxygen delivery to the patient and does not contribute to the oxygenation of the patient. 7 Recirculation has been found to be 53% at a bypass flow of 400 ml/min. Generally, as recirculation increases, the efficacy to the systemic circulation decreases in terms of oxygen delivery.…”
Section: Discussionmentioning
confidence: 94%
“…2,5 Recirculation during VVECLS had previously been measured and quantified by various methods to achieve a reduction. 7,8 In this preliminary experiment, we calculated the recirculation by the gold standard method.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Sreenan et al 10 demonstrated recirculation rates ranging from 30% to 70% with pump flows of 200-500 ml/min in a venovenous circuit via a unicaval dual-lumen cannula. In a study comparing different methods of calculating recirculation, consistent relationships with high correlation coefficients were identified for each of the ultrasound dilution, SvO 2 , and central venous line (CVL) methods (% recirculation = 1.88 + 0.23 × ECMO flow, r = 0.99; 1.42 + 0.32 × ECMO flow, r = 0.99; and 6.66 + 0.36 ×ECMO flow, r = 0.96, respectively).…”
Section: Pump Speed Cannula Size and Extracorporeal Blood Flowmentioning
confidence: 99%
“…In a study comparing different methods of calculating recirculation, consistent relationships with high correlation coefficients were identified for each of the ultrasound dilution, SvO 2 , and central venous line (CVL) methods (% recirculation = 1.88 + 0.23 × ECMO flow, r = 0.99; 1.42 + 0.32 × ECMO flow, r = 0.99; and 6.66 + 0.36 ×ECMO flow, r = 0.96, respectively). 8 The relationship between ECMO blood flow rates and recirculation may, in part, be explained by an increase in negative venous pressures within the venous drainage limb that occurs at higher flow rates. 11 Relatively larger drainage cannulae may allow for comparable blood flow rates at lower pump speeds with less negative venous pressure, potentially mitigating the amount of recirculation (Figures 3 and 4).…”
Section: Pump Speed Cannula Size and Extracorporeal Blood Flowmentioning
confidence: 99%
See 1 more Smart Citation